Intracardiac Acoustic Radiation Force Impulse Imaging: A Novel Imaging Method for Intraprocedural Evaluation of Radiofrequency Ablation Lesions: Feasibility of intraprocedure ARFI imaging of RFA - Eyerly, Stephanie A. (2012)
BACKGROUND: Arrhythmia recurrence after cardiac radiofrequency ablation (RFA) for atrial fibrillation (AF) has been linked to conduction through discontinuous lesion lines. Intraprocedural visualization and corrective ablation of lesion line discontinuities could decrease post-procedure AF recurrence. Intracardiac acoustic radiation force impulse (ARFI) imaging is a new imaging technique that visualizes RFA lesions by mapping the relative elasticity contrast between compliant-unablated and stiff-RFA treated myocardium. OBJECTIVE: To determine if intraprocedure ARFI images can identify RFA treated myocardium in vivo. METHODS: In eight canines, an electroanatomical mapping (EAM) guided intracardiac echo catheter (ICE) was used to acquire 2D ARFI images along right atrial ablation lines before and after RFA. ARFI images were acquired during diastole with the myocardium positioned at the ARFI focus (1.5 cm) and parallel to the ICE transducer for maximal and uniform energy delivery to the tissue. Three reviewers categorized each ARFI image as depicting no lesion, non-contiguous, or contiguous lesion. For comparison, three separate reviewers confirmed RFA lesion presence and contiguity based on functional conduction block at the imaging plane location on EAM activation maps. RESULTS: Ten percent of ARFI images were discarded due to motion artifacts. Reviewers of the ARFI images detected RFA-treated sites with high sensitivity (95.7%) and specificity (91.5%). Reviewer identification of contiguous lesion had 75.3% specificity and 47.1% sensitivity. CONCLUSIONS: Intracardiac ARFI imaging was successful in identifying endocardial RFA treatment when specific imaging conditions were maintained. Further advances in ARFI imaging technology would facilitate a wider range of imaging opportunities for clinical lesion evaluation.